Water Use and Productivity of Corn and Grain Sorghum in Long-Term Crop Sequences - R. M. Aiken (Kansas Agricultural Experiment Station Research Reports, 2020)
Dryland corn and grain sorghum showed similar water productivity of grain and above-ground biomass, relative to respective growing periods, at the apparent yield frontier. The yield frontier indicates the maximum productivity for a given amount of water use. This similarity in productive response to water supply provides a foundation for improved precipitation use. Yield gaps relative to the yield frontier appear substantial. Water supply during the grain filling period was the primary driver of feed grain crop productivity, and was affected more by available soil water at pollen shed than by precipitation during grain-fill or available water at maturity. Grain sorghum and corn differed in responses to annual conditions, offering potential for risk management.
Keywords: corn; grain sorghum; water use; dryland; cropping system